Musikalsk mening – Starting all over again…: Tobias Norlind-föreläsning, Stockholm 12. juni 2007 - Weisethaunet, Hans (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2008)
Music and Meaning: Starting all over again... This article discusses various approaches to the issue of music and meaning and argues that neither ”meaning” nor ”emotions” that relate to the processes of musical experience can be explained by causal models. The article does not seek to provide any finite answers to the much debated questions concerning music and meaning, but based on examples from the author’s research, including work on music criticism, it argues that ”meaning” is constructed through interpretative processes that are cultural and temporal, i.e. tied to time, place and space. The article was presented as the Tobias Norlind lecture 2007 hosted by The Swedish Society for Musicology, at the University of Stockholm, June 12, 2007.